4CPS-024 Efficacy, safety and acceptance of treatment with alirocumab or evolocumab in patients with dyslipidaemia. (March 2019) - Monge, I; Acin, P; Navarrete-Rouco, E; Recasens, L; Pedro-Botet, J; Oliveras, A; González-Colominas, E; Luque, S; Grau, S
Abstract : Background: Alirocumab and evolocumab are two monoclonal antibodies proproteinconvertasesubtilisin/kexin type 9 inhibitors (iPCSK9) approved for the treatment of hypercholesterolaemia. Purpose: Evaluation of the efficacy, safety and patient acceptance of treatment with iPCSK9 in a cohort of patients with dyslipidaemia. Material and methods: Retrospective observational study performed in a university hospital. Included patients started with iPCSK9 therapy from September 2016 to June 2018. Data collected: demographic; iPCSK9 dose; prevention; indication; cardiovascular risk factors (CVRF) (excluding dyslipidaemia), cardiovascular risk (CVR) (by ESC 2016 guidelines); and statin intolerance. At baseline (pre) and 6–12 weeks after starting treatment (post), LDL value and concomitant lipid lowering agents (LLA) were collected. Additionally, reported adverse events and patient treatment were evaluated through a validated survey 1 during the pharmaceutical visit. Statistics: Categorical variables: n (%), Fisher's exact test. Quantitative variables: mean ±SD/median(rank), Mann–Whitney U test. Results: *Pseudogrippal syndrome (3) and constipation (1). All patients decreased LDL except 1 patient on alirocumab who was non-adherent. Post: 15 treatment changes in 13 (27.1%) patients with alirocumab (five (33.3%) alirocumab dose increase, seven (46.7%) other LLA introduction/dose increase, three (20.0%) other LLA suspension/dose decrease). With evolocumab patients, only 1 stopped ezetimibe. After the survey, all patients desired to continue with iPCSK9. Conclusion: After 6–12 weeks of iPCSK9 treatment, all patients reduced LDL level except 1 who was non-adherent. The LDL reduction ranged between 54%–71% and all patients on evolocumab achieved a LDL <70 mg/dL. The tolerability was excellent and only mild adverse events in about 8% of patients were experienced. A high acceptance of both alirocumab and evolocumab was reported by all patients who would continue with iPCSK9 treatment. References and/or acknowledgements: No conflict of interest.